Analysis of Amil Zakat Institutions Financial Performance Prior and During Covid-19 - Faris Shalahuddin Zakiy; Eqi Suciati; Najim Nur Fauziah (Muhammadiyah University Press, 2022)
This study aims to measure the performance of amil zakat institutions using activity ratios, efficiency ratios, amil fund ratios, liquidity ratios, and growth ratios before and during covid-19. Besides, this paper also explores the extent of the impact of covid-19 on the performance of amil zakat institutions. This paper is a qualitative research study with a case study approach in Lazismu of the Central Java region. The case was raised from Lazismu financial statements in 2019 and 2020. The financial statements are measured and reviewed using ratios to describe in-depth financial performance. The findings of this study provide the results of calculations of the five ratios, including activity ratios, efficiency ratios, amil funds ratios, liquidity ratios and growth ratios. It shows good performance, efficiency, and a significant increase. The overall performance of the Lazismu central Java region is stable and tends to increase during covid-19, and its performance does not differ much before covid-19.